OPEN-ENDED APPROACH: AN EFFORT IN CULTIVATING STUDENTS' MATHEMATICAL CREATIVE THINKING ABILITY AND SELF-ESTEEM IN MATHEMATICS - Abdul Fatah; Didi Suryadi; Jozua Sabandar; Turmudi Turmudi (Department of Doctoral Program on Mathematics Education, Sriwijaya University, 2016)
The present study aims at examining the use of open-ended approach in cultivating senior high school students' mathematical creative thinking ability (MCTA) and self-esteem (SE) in mathematics viewed from school category. The subjects of this research were the students grade XI at three schools; high, middle and low category in Kota Serang, Banten Province. In every school category, two classes were chosen; one class was the experimental group which was taught by open-ended approach, while another class was a control group which was taught by conventional way. This quasi-experimental research employed MCTA test and SE in mathematics scale as the instruments. In general, the research result shows that the MCTA improvement and SE level of the students who are taught by open-ended approach is better than those who are taught conventionally. The results of students' MCTA and SE viewed from school category will be further discussed.Keywords: mathematical creative thinking ability, self-esteem, open-ended approach